2010
DOI: 10.1371/journal.pone.0014162
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Dopamine D4 Receptor Gene Variation with Both Infidelity and Sexual Promiscuity

Abstract: BackgroundHuman sexual behavior is highly variable both within and between populations. While sex-related characteristics and sexual behavior are central to evolutionary theory (sexual selection), little is known about the genetic bases of individual variation in sexual behavior. The variable number tandem repeats (VNTR) polymorphism in exon III of the human dopamine D4 receptor gene (DRD4) has been correlated with an array of behavioral phenotypes and may be predicatively responsible for variation in motivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
15

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 44 publications
(66 reference statements)
2
60
0
15
Order By: Relevance
“…In humans, individual differences in attachment style, fidelity, and sociosexuality are known to have a hereditary basis (26)(27)(28)(29). The degree to which variation in physiological mechanisms of attachment (30,31) and of sexual arousal (32,33) is shared between the sexes is not sufficiently known to predict whether between-sex correlations can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, individual differences in attachment style, fidelity, and sociosexuality are known to have a hereditary basis (26)(27)(28)(29). The degree to which variation in physiological mechanisms of attachment (30,31) and of sexual arousal (32,33) is shared between the sexes is not sufficiently known to predict whether between-sex correlations can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Recent behavioral-genetic models confirm a common genetic factor for certain personality characteristics and risky sexual attitudes (Zietsch et al, 2010). Other analyses suggest genetic underpinnings for both novelty-seeking characteristics (Munafò, Yalcin, WillisOwen, & Flint, 2008) and a range of sexual attitudes and preferences (Ben Zion et al, 2006;Garcia et al, 2010;Halpern, Kaestle, Guo, & Hallfors, 2007).…”
Section: Male Bisexual Identity Sexual Curiosity and Sexual Arousalmentioning
confidence: 99%
“…Genotypes related to dopamine signaling predict personality characteristics such as sensation seeking and risk-taking (Lobo et al, 2010) and a wide range of novelty-seeking traits (Munafò et al, 2008). Dopamine-related genotypes also predict a variety of sexual characteristics, including promiscuity (Garcia et al, 2010), number of sex partners (Halpern et al, 2007) and sexual arousal (Ben Zion et al, 2006). Specific forms of dopamine receptor genes, related to sensation seeking, appear to be common in men with bisexual experiences (Hamer & Copeland, 1994).…”
Section: High Sexual Curiosity and Bisexual Arousalmentioning
confidence: 99%
“…Population differences in dopamine receptor (DRD4) genetic polymorphisms exist, with possible explanations advanced to account for those differences including genetic drift, adaptive migration, and mating behavior (Harpending and Cochran, 2002). A U.S. study found that polymorphisms in this same system were associated with differences in sexual promiscuity in a university sample (Garcia et al, 2010).…”
Section: Recent Genetic Genomic and Physiological Datamentioning
confidence: 99%